2022
DOI: 10.2196/32694
|View full text |Cite|
|
Sign up to set email alerts
|

The Transition of Social Isolation and Related Psychological Factors in 2 Mild Lockdown Periods During the COVID-19 Pandemic in Japan: Longitudinal Survey Study

Abstract: Background Lockdowns and stay-at-home orders announced internationally for COVID-19 have led to physical and social distancing, with reports of many individuals experiencing social isolation (SI) and loneliness. Although the emergency declaration in Japan was declared as a “mild” lockdown requested by the government without penalties for violations, the lockdown measures, including SI, had several influences on people’s lives and mental health as in other countries. Furthermore, Japan declared a st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The responses included seven options: “almost every day (6–7 times a week),” “4–5 times a week,” “2–3 times a week,” “once a week,” “2–3 times a month,” “once a month,” and “rarely.” The total frequency of contact was calculated based on a previous article ( 7 ). We applied the sum of the frequency of contact using the eight questions and regarded contacts less than once a week in the total frequency of contact as social isolation because people who had contacts less than once a week were reportedly more likely to have higher risks of all-cause mortality and onset of dementia and disability ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses included seven options: “almost every day (6–7 times a week),” “4–5 times a week,” “2–3 times a week,” “once a week,” “2–3 times a month,” “once a month,” and “rarely.” The total frequency of contact was calculated based on a previous article ( 7 ). We applied the sum of the frequency of contact using the eight questions and regarded contacts less than once a week in the total frequency of contact as social isolation because people who had contacts less than once a week were reportedly more likely to have higher risks of all-cause mortality and onset of dementia and disability ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, poorer levels of social isolation and loneliness were observed during the strict lockdown periods, whereas better levels were observed during the reopening phases. Sugaya et al reported no improvement in social isolation and loneliness between May 2020 and February 2021 among Japanese people, whereas psychological distress and depression significantly decreased ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this "mild lockdown" [15] in Japan still affected people's lives in many ways, including lifestyle changes due to remote working and online learning as well as financial hardship due to reduced income and unemployment [16]. Indeed, the prolonged COVID-19 pandemic and repeated declarations of a state of emergency were responsible for maintaining the unfavorable psychological state of the Japanese population [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several previous studies have suggested that not all psychosocial variables may have changed uniformly during the pandemic. For example, no improvements were observed in severe social isolation or loneliness among the Japanese population 7 between the two survey phases, although psychological distress improved significantly and depression decreased slightly.…”
Section: Background and Summarymentioning
confidence: 92%